Expanding preconception carrier screening for the Jewish population using high throughput microfluidics technology and next generation sequencing - Gal, Moran (BMC Med Genomics, 2016)
BACKGROUND: Genetic screening to identify carriers of autosomal recessive diseases has become an integral part of routine prenatal care. In spite of the rapid growth of known mutations, most current screening programs include only a small subset of these mutations, and are performed using diverse molecular techniques, which are generally labor-intensive and time consuming. We examine the implementation of the combined high-throughput technologies of specific target amplification and next generation sequencing (NGS), for expanding the carrier screening program in the Israeli Jewish population as a test case. METHODS: We compiled a panel of 370 germline mutations, causing 120 disorders, previously identified in affected Jewish individuals from different ethnicities. This mutation panel was simultaneously captured in 48 samples using a multiplex PCR-based microfluidics approach followed by NGS, thereby performing 17,760 individual assays in a single experiment. RESULTS: The sensitivity (measured with depth of at least 50×) and specificity of the target capture was 98 and 95 % respectively, leaving minimal rate of inconclusive tests per sample tested. 97 % of the targeted mutations present in the samples were correctly identified and validated. CONCLUSION: Our methodology was shown to successfully combine multiplexing of target specific primers, samples indexing and NGS technology for population genetic screens. Moreover, it’s relatively ease of use and flexibility of updating the targets screened, makes it highly suitable for clinical implementation. This protocol was demonstrated in pre-conceptional screening for pan-Jewish individuals, but can be applied to any other population or different sets of mutations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12920-016-0184-7) contains supplementary material, which is available to authorized users.